Heterozygous p.S811F RET gene mutation associated with renal agenesis, oligomeganephronia and total colonic aganglionosis: a case report. Issue 1 (December 2016) - Sugimoto, Keisuke; Miyazawa, Tomoki; Nishi, Hitomi; Miyazaki, Kohei; Enya, Takuji; Okada, Mitsuru; Takemura, Tsukasa
Abstract Background Several shared common gene networks participate in development of interstinal ganglia and also nephron formation; the glial cell line-derived neurotrophic factor/Ret/glial cell line-derived neurotrophic factor receptor gene network is particularly important. Case presentation We encountered a patient with total colonic aganglionosis as well as right renal agenesis and oligomeganephronia. Gene analysis in this patient disclosed a heterozygous p.S811F mutation was in Ret gene exon 14, resulting in a substitution of phenylalanine for serine. The large side chain of phenylalanine obstructed the opening of the hydrophobic pocket of the Ret molecule causing interference with its interaction with adenosine triphosphate and consequent marked reduction in its enzyme activity. This could account for our patient's severe intestinal disease and renal dysplasia. We know of no previous reports of concomitant Hirschsprung's disease and oligomeganephronia. Conclusions The patient's overall illness could be considered a novel Ret gene mutation syndrome.